2012
DOI: 10.1007/s00383-012-3213-4
|View full text |Cite
|
Sign up to set email alerts
|

Implantable versus cuffed external central venous catheters for the management of children and adolescents with acute lymphoblastic leukaemia

Abstract: When patients are risk-stratified for disease severity there is no difference in rates of CVC removal prior to completion of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
2
16
1
Order By: Relevance
“…Twelve studies 59,61,66,67,72,76,82,83,89,97,105,121 described the outcome of CVADassociated BSI without the clarity and rigor of benchmarked standards, which meant that their CVAD-associated BSI data were not included in the review. Two studies 30,116 provided combined "all-type" infection or mechanical failure outcomes, instead of providing separated local and systemic infection, occlusion, and dislodgement data.…”
Section: Study Qualitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies 59,61,66,67,72,76,82,83,89,97,105,121 described the outcome of CVADassociated BSI without the clarity and rigor of benchmarked standards, which meant that their CVAD-associated BSI data were not included in the review. Two studies 30,116 provided combined "all-type" infection or mechanical failure outcomes, instead of providing separated local and systemic infection, occlusion, and dislodgement data.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…These data also were not included in the review. We were unable to ascertain the number of catheter days in 23 studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]84,85,92,97,99,122 which excluded their data from contributing to the meta-analysis reporting failure and complications per 1000 catheter days. Because of a lack of data, the rate of CVAD failure per 1000 catheter days for nontunneled, percutaneous CVADs could not be estimated.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…Since lumen diameter and number corresponded with the CVAD-type, these were also excluded in the multivariate analyses. Disease severity of the underlying malignancy and the associated longer neutropenia episodes have been associated with the incidence of, and removal owing to CLABSI [16,22,28]. Disease severity was therefore investigated by scoring the presence of severe neutropenia, a neutrophil granulocyte count of less than 100 × 106 /L, during CLABSI in the HB-CVAD group compared to the TIVAP group.…”
Section: Definitions and Outcome Measurementsmentioning
confidence: 99%
“…This finding was in keeping with a meta‐analysis of adult studies that identified a higher rate of thrombosis in PICC lines, particularly in adults who were critically ill or had malignancy (Chopra et al , ), although more recent data in adults have shown a lower risk of thrombosis compared with traditional CVLs in a population with acute leukaemia (Cerchione et al , ). Thrombosis occurs less frequently in association with internal lines (ports) than external tunnelled lines, such as Hickman or Broviac catheters (McClean et al , ; White et al , ; Mangum et al , ). A multicentre randomised controlled trial (RCT) in adults with malignancy, comparing complication rates between external tunnelled lines, ports and PICCs for the administration of chemotherapy, is currently ongoing [Cancer and Venous Access (CAVA); ISRCTN 44504648].…”
Section: Reducing the Risk Of Vtementioning
confidence: 99%